Research on invasive pests and diseases in New Zealand and the law - Teulon, David; Wilson, Boyd; Holton, A; Ridley, G (New Zealand Science Review, 2013)
​Two New Zealand statutes have important implications for research with organisms not previously found in New Zealand and either incidentally or illegally introduced. The Biosecurity Act 1993 and the Hazardous Substances and New Organisms Act 1996 define the legal framework and allowable activities for ‘unwanted’ and ‘new’ organisms, respectively. Aspects of these Acts that are relevant to research activities possible with plant pest and disease organisms after their discovery, in particular those organisms requiring rapid development of management strategies and tools, are summarised. The need for accurate, detailed and accessible lists of ‘unwanted’ and ‘new’ organisms, and the need for the Ministry for Primary Industries and the Environmental Protection Authority to respond rapidly when the status of these organisms needs to be changed is highlighted. Consideration should be given to making the legislation concerning ‘new’ organisms more applicable to incidentally or illegally introduced organisms.